A 3-year-old boy with kyphosis, back mass and weakness. - Oberdorfer P. (2017)
Spinal tuberculosis (TB) in children is uncommon. The authors report a case of a 3-year-old boy who was diagnosed with TB spondylitis. He presented to the hospital with a back mass, back pain and inability to walk. He failed to receive TB prophylaxis after having been in close contact to his mother who had pulmonary TB. He received incision and drainage and continued on anti-TB regimens without complications. At 4-month follow-up, he was able to stand and walk without assistance. It is important to carry out contact investigations and provide TB prophylaxis to children who have had a history of contacting TB index cases to prevent TB disease and serious complications of TB infection.